Second breast conserving therapy after ipsilateral breast tumor recurrence - a 10-year experience of re-irradiation - Forster, Tobias; Akbaba, Sati; Schmitt, Daniela; Krug, David; El-Shafie, Rami; Oelmann-Avendano, Jan Tobias; Lindel, Katja; König, Laila; Arians, Nathalie; Bernhardt, Denise; Marmé, Frederik; Schneeweiss, Andreas; et al. (Journal of contemporary brachytherapy, 2019)
Purpose: The aim of this study is to evaluate the efficacy and toxicity of post-operative partial breast re-irradiation with multi-catheter brachytherapy after second breast conserving therapy (BCT) in patients with small, low-risk ipsilateral breast tumor recurrence (IBTR).